The Complexity of Urban Eco-evolutionary Dynamics. (26th August 2020) - Alberti, Marina; Palkovacs, Eric P; Roches, Simone Des; Meester, Luc De; Brans, Kristien I; Govaert, Lynn; Grimm, Nancy B; Harris, Nyeema C; Hendry, Andrew P; Schell, Christopher J; Szulkin, Marta; Munshi-South, Jason; et al.
Abstract: Urbanization is changing Earth's ecosystems by altering the interactions and feedbacks between the fundamental ecological and evolutionary processes that maintain life. Humans in cities alter the eco-evolutionary play by simultaneously changing both the actors and the stage on which the eco-evolutionary play takes place. Urbanization modifies land surfaces, microclimates, habitat connectivity, ecological networks, food webs, species diversity, and species composition. These environmental changes can lead to changes in phenotypic, genetic, and cultural makeup of wild populations that have important consequences for ecosystem function and the essential services that nature provides to human society, such as nutrient cycling, pollination, seed dispersal, food production, and water and air purification. Understanding and monitoring urbanization-induced evolutionary changes is important to inform strategies to achieve sustainability. In the present article, we propose that understanding these dynamics requires rigorous characterization of urbanizing regions as rapidly evolving, tightly coupled human–natural systems. We explore how the emergent properties of urbanization affect eco-evolutionary dynamics across space and time. We identify five key urban drivers of change—habitat modification, connectivity, heterogeneity, novel disturbances, and biotic interactions—and highlight the direct consequences of urbanization-driven eco-evolutionary change for nature's contributions to people. Then, we explore five emerging complexities—landscape complexity, urban discontinuities, socio-ecological heterogeneity, cross-scale interactions, legacies and time lags—that need to be tackled in future research. We propose that the evolving metacommunity concept provides a powerful framework to study urban eco-evolutionary dynamics.